Baseline podocyte‐associated state and persistent cell–matrix transcriptional programs are associated with BALB /c substrain differences in adriamycin nephropathy - Ryuya Nakagawa; Masaki Watanabe; Koyuki Kawamoto; Momoka Hiratsuka; Takeru Sasaki; Nobuya Sasaki (Animal Models and Experimental Medicine, 2026)
Abstract Background Adriamycin (ADR)‐induced nephropathy is a widely used murine model of glomerular injury. Although strain‐dependent susceptibility is well recognized, variation among closely related substrains remains insufficiently explored. Methods We compared early responses to ADR between two BALB/c substrains, BALB/cAJcl (AJcl) and BALB/cByJcl (ByJcl), focusing on baseline podocyte‐associated features and early glomerular transcriptional programs. Results Following ADR administration, ByJcl mice developed significantly greater albuminuria at Day 7 compared with AJcl mice. At Day 7, ByJcl mice also showed lower WT1‐positive nuclei counts and diminished nephrin immunoreactivity than AJcl mice; notably, these differences were already evident at baseline. Glomerulus‐enriched RNA sequencing showed that extracellular matrix organization and integrin signaling were already enriched in ByJcl at baseline and remained enriched at Day 5, when coordinated suppression of podocyte‐associated transcriptional programs was also evident. Conclusion Substrain‐dependent differences in baseline podocyte‐associated readouts and a pre‐existing cell–matrix transcriptional state that persists after ADR are associated with divergent trajectories of ADR‐induced injury. Because WT1‐based counts cannot distinguish podocyte number from WT1 expression, these baseline differences are best described as an attenuated podocyte‐associated state rather than a definitive reduction in podocyte number. Careful documentation of substrain origin is critical for experimental reproducibility in nephropathy research.